2010
DOI: 10.1161/atvbaha.110.204453
|View full text |Cite
|
Sign up to set email alerts
|

Vasoprotective and Atheroprotective Effects of Angiotensin (1-7) in Apolipoprotein E–Deficient Mice

Abstract: Long-term Ang (1-7) treatment caused both vasoprotection, via improvement in endothelial function, and atheroprotection, with a reduction in lesion progression in a model of atherosclerosis. These effects appear to be mediated by the restoration of nitric oxide bioavailability and involve a complex interaction of both Mas and AT(2) receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
132
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 52 publications
12
132
1
1
Order By: Relevance
“…In a chronic setting, the athero-protective effect of Ang-(1-7) was abrogated by an AT2R antagonist. 18 These findings suggest a functional and possibly physical interaction between Mas receptor and AT2R in the vascular system. 11 We found that Ang-(1-7) reduced expression of IL-1β and TNF-α in cerebral arteries.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In a chronic setting, the athero-protective effect of Ang-(1-7) was abrogated by an AT2R antagonist. 18 These findings suggest a functional and possibly physical interaction between Mas receptor and AT2R in the vascular system. 11 We found that Ang-(1-7) reduced expression of IL-1β and TNF-α in cerebral arteries.…”
Section: Discussionmentioning
confidence: 87%
“…It can reduce vascular inflammation, oxidative stress, cell proliferation, and nitric oxide availability, thereby reducing atherosclerosis and enhancing plaque stability. 18,21 It possesses a high binding capacity to Mas receptor, a G proteincoupled receptor that appears to mediate many of the biologic effects of Ang-(1-7). 7,9 Although the binding affinity of AT2R with Ang-(1-7) is relatively weak, AT2R appears to mediate some of the vascular effects of Ang- (1-7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 However, whether Ang II receptors are involved in Ang-(1-7)-stimulated effects is still under debate because some of the stimulated pathways are also affected by co-treatment with AT 1 blockers 22,23 or AT 2 blockers. 24,25 To further characterize the impact of Ang II receptor subtypes on Ang-(1-7) mediated vascular relaxation, we investigated the cardiovascular response to acute Ang-(1-7) infusion in recently generated mice lacking one, two or all three Ang II receptor subtypes. 26 …”
Section: Introductionmentioning
confidence: 99%